The Prevalence of Genital Human Papillomavirus Subtypes in a Cohort of Hispanic Women Presenting for Cervical Cancer Screening Along the US-Mexico Border. (10th September 2020) - Shokar, Navkiran K.; Doan, Amy; Calderon-Mora, Jessica; Lakshmanaswamy, Rajkumar; Ramadevi, Subramani; Shokar, Gurjeet S.; Molokwu, Jennifer; Alomari, Adam; Dwivedi, Alok
Introduction : Hispanic women residing along the US-Mexico border have the highest cervical cancer incidence rates in the US. Genital human papillomavirus (HPV) is the major causative agent, but more information is needed about the prevalence and distribution of genital HPV subtypes in this high-risk population.Methods : A population-based cross-sectional study of uninsured Hispanic women along the US-Mexico border was conducted and participants had their cervical specimens undergo DNA extraction followed by HPV genotype testing using the Linear Assay from Roche® Diagnostics, to identify 37 genital HPV subtypes.Results : Among the 585 women aged 21-65 years, 584 self-identfied as Hispanic. Any HPV subtype prevalence was 53.2% (95% CI: 49.0%-57.3%) and of these 52% (i.e. 27.5% of the total) had single infections and 48% (i.e. 25.6% of the total) had multiple infections. High-risk HPV prevalence was 15.6% (95% CI: 24-31.3%). The mean number of subtypes among those testing positive was 2.1 (SD 1.6). The prevalence of any HPV and high-risk HPV showed a U shaped pattern with age; and prevalence of 16/18 and non-16/18 high-risk subtypes (e.g. 31, 33, 35, 39, 45, 51, 52, 58); also varied with age. Forty-one percent of high-risk HPV occurrences were of a subtype not covered by the current nonavalent HPV vaccine.Discussion : Our findings suggest a different high-risk HPV subtype pattern and age distribution among Hispanic women in the USA, which could have implications for future cervical cancer prevention strategies.